Competitive-level and leg preference effects on vertival ground reaction forces in soccer kicking - Zhang, Y.; Navandar, A.; Navarro, E. (ISBS Proceedings Archive: Vol. 43: Iss. 1, 2025)
This study explored the effect of the competitive level and leg preference on the vertical ground reaction force (vGRF) during instep soccer kicking, and its relationship on ball velocity. Seventy-eight players belonging to four different competitive levels (female professional, male professional, male elite youth, and male non-elite youth) performed maximal instep kicks with their preferred and non-preferred legs from which the ball velocity and the vGRF were collected. The results showed that higher-level players and preferred leg kicks exhibited a double-peak vGRF pattern, but lower-level players and non-preferred kicks exhibited a single-peak vGRF pattern. The vGRF had a weak to moderate positive correlation with ball velocity (r = 0.27-0.46). These findings highlight the importance of support leg mechanics in optimizing kicking performance.